1972
DOI: 10.1017/s0021859600032287
|View full text |Cite
|
Sign up to set email alerts
|

The yield and composition of the milk of Finnish Landrace × Blackface ewes: I. Ewes and lambs maintained indoors

Abstract: Twenty-two Finnish Landrace x Blackface ewes suckling either single, twin, triplet or quadruplet lambs were maintained indoors during a 12-week lactation period. Milk production was estimated at weekly intervals by hand milking following oxytocin administration. Milk was collected from each ewe in four similar volumetric portions which were retained in order of withdrawal and analysed for maj or constituents. Weighted volumes of milk from each of the four portions were bulked to give a single sample for analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
11
1
1

Year Published

1977
1977
1996
1996

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 18 publications
9
11
1
1
Order By: Relevance
“…This value is within the range reported in other studies, such as 25% (Addleman et al, 1964), 22% (Barnicoat et al, 1949b), 22% , 13 to 33% , 35% (Peart et al, 1972) and 18 to 41% (Slen et al, 1963). The ability of twin lambs to more completely evacuate the udder early in lactation has been cited as the main factor explaining this difference .…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This value is within the range reported in other studies, such as 25% (Addleman et al, 1964), 22% (Barnicoat et al, 1949b), 22% , 13 to 33% , 35% (Peart et al, 1972) and 18 to 41% (Slen et al, 1963). The ability of twin lambs to more completely evacuate the udder early in lactation has been cited as the main factor explaining this difference .…”
Section: Resultssupporting
confidence: 88%
“…The reverse tendency was observed in a later study with Hampshire and Corriedale ewes, even though the difference was not statistically significant. Peart et al (1972) concluded that number of lambs suckled did substantially influence fat and protein content of the 8 milk; ewes nursing triplets had the highest percent of milk fat followed by ewes nursing twins and then by ewes nursing singles. This order was reversed for milk protein percent.…”
Section: Resultsmentioning
confidence: 99%
“…Protein percentages were generally similar among ewes with singles or twins mable 3). Lower milk protein levels associated with suckling twins have been reported earlier (Gardner and Hogue, 1964;Peart et al, 1972).…”
Section: Us Sheep Experiments Station Have Beensupporting
confidence: 65%
“…The 20-22% initially greater udder weight of twin-bearing ewes and associated 11-13% greater average milk yield during the 6-week period are real effects of pregnancy status since all ewes were either machine-milked or suckled by twin lambs. The differences, though much smaller than those expected between ewes rearing twin v. single lambs (Wallace, 1948;Coop & Drew, 1963;Peart, 1967;Peart, Edwards & Donaldson, 1972;Geenty, 1979), are interesting physiologically.…”
Section: Discussionmentioning
confidence: 77%